Serum levels of TNF-a and IFN-g gene polymorphism in type 2 diabetes mellitus in kurdish patients - Darogha, Suhaila Nafee (Cellular and Molecular Biology, 2021)
Type 2 diabetes mellitus (T2DM) is a metabolic disease and cytokines show a vital role in the T2DM progress. The goal of this research was to assess serum levels of tumor necrosis factor-alpha (TNF-?) and interferon-gamma (IFN-?) gene polymorphism in T2DM in Kurdish patients. Levels of serum IFN-? and TNF-? were assessed through enzyme-linked immune sorbent assay in individuals with T2DM and the control group. DNA was extracted and the amplification refractory mutational system method was utilized for genotyping the IFN-? (+874) A/T and TNF-? (-308) G/A. The Hardy–Weinberg equilibrium was evaluated with the ?2-test. The IFN- ? serum levels were significantly different between patients with T2DM and control individuals (P<0.05). But the C-reactive protein (CRP) and TNF-? serum levels were not significantly different between them (P>0.05). The serum level of IFN- ? (+874) AT genotype and TNF-? (- 308) GG genotypes were significantly higher in the T2DM group comparing with healthy people (P<0.05). A significant relation between T2DM and IFN-? (+874) gene polymorphism’s TT and AT genotypes was observed. Also, it was not a significant relation between TNF-? (?308) gene polymorphism’s GG and GA genotypes and T2DM. But the statistically significant difference was found in the genotype AA frequency. Genetic polymorphisms of IFN-? (+874) and TNF-? (?308) are contributed to the genetic susceptibility for T2DM development in the Kurdish population. Early screening of these two genetic polymorphisms may assist in the early control and management of T2DM.